Adipocytes play an etiological role in the podocytopathy of high-fat diet-fed rats. Issue 2 (November 2016) - Chen, Jinn-Yang; Jian, Deng-Yuan; Lien, Chih-Chan; Lin, Yu-Ting; Ting, Ching-Heng; Chen, Luen-Kui; Hsu, Ting-Chia; Huang, Hsuan-Min; Wu, Yu-Ting; Kuan, Tse-Ting; Chao, Yu-Wen; Wu, Liang-Yi; et al.
Abstract : Obesity is a risk factor that promotes progressive kidney disease. Studies have shown that an adipocytokine imbalance contributes to impaired renal function in humans and animals, but the underlying interplay between adipocytokines and renal injury remains to be elucidated. We aimed to investigate the mechanisms linking obesity to chronic kidney disease. We assessed renal function in high-fat (HF) diet-fed and normal diet-fed rats, and the effects of preadipocyte- and adipocyte-conditioned medium on cultured podocytes. HF diet-fed and normal diet-fed Sprague Dawley rats were used to analyze the changes in plasma BUN, creatinine, urine protein and renal histology. Additionally, podocytes were incubated with preadipocyte- or adipocyte-conditioned medium to investigate the effects on podocyte morphology and protein expression. In the HF diet group, 24 h urinary protein excretion (357.5 ± 64.2 mg/day vs 115.9 ± 12.4 mg/day, P < 0.05) and the urine protein/creatinine ratio were significantly higher (1.76 ± 0.22 vs 1.09 ± 0.15, P < 0.05), increased kidney weight (3.54 ± 0.04 g vs 3.38 ± 0.04 g, P < 0.05) and the glomerular volume and podocyte effacement increased by electron microscopy. Increased renal expression of desmin and decreased renal expression of CD2AP and nephrin were also seen in the HF diet group ( P < 0.05). Furthermore, we found that adipocyte-conditioned medium-treated podocytes showed increased desmin expression and decreased CD2AP and nephrin expression compared with that in preadipocyte-conditioned medium-treated controls ( P < 0.05). These findings show that adipocyte-derived factor(s) can modulate renal function. Adipocyte-derived factors play an important role in obesity-related podocytopathy.